Methods for the Assessment of Environmental Sustainability of Packaging: A review - Pauer, Erik; Heinrich, Victoria; Tacker, Manfred (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2017)
Growing awareness for environmental issues and stricter legislation increases the pressure on producers to address these issues. In particular, packaging is under scrutiny, because it is perceived as a major contributor to waste streams and resulting environmental problems. This review provides an overview of the existing tools used to assess the environmental impacts of packaging. While a full life cycle assessment (LCA) is an appropriate tool to assess the impacts of a well-established product, simplified LCA allows a quick and less detailed assessment during, for example, the design phase of a certain product. Furthermore, scorecards are capable of addressing pre-selected environmental aspects of packaging. Whenever applying simplified LCA or scorecards, the inevitable trade-off between accuracy and user-friendliness has to be considered. Nevertheless, a careful selection of the indicators to be assessed and a good understanding of the packaging system allow results to be meaningful even with these simplified tools.